2019
DOI: 10.16970/entoted.499460
|View full text |Cite
|
Sign up to set email alerts
|

Population development of Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) in vineyards of Çanakkale Province

Abstract: The spotted wing drosophila, Drosophila suzukii (Matsumura) (Diptera: Drosophilidae), is one of the important invasive pests of cultivated berry and stone fruits worldwide. The purpose of this study was to determine the population growth of D. suzukii in vineyards in Çanakkale Province from 2014 to 2017. The numbers of D. suzukii male and female individuals caught in the bait traps were recorded weekly. Drosophila suzukii population started to emerge from late September to February in all years. The maximum po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…A total of 304 traps were hung on during the study and the number of adult flies caught by the traps was 255 in 2017, and 2128 in 2018. Similarly to the first year of this research, Kasap and Özdamar (2019) also reported that the first D. suzukii adults were detected in September of all years. Yet, accordingly to Thistlewood et al (2018), due to the fact that winter of 2017 was warmer than in the previous year, the emergence of adult D. suzukii in the latter year occurred earlier than 2017.…”
Section: Resultssupporting
confidence: 81%
“…A total of 304 traps were hung on during the study and the number of adult flies caught by the traps was 255 in 2017, and 2128 in 2018. Similarly to the first year of this research, Kasap and Özdamar (2019) also reported that the first D. suzukii adults were detected in September of all years. Yet, accordingly to Thistlewood et al (2018), due to the fact that winter of 2017 was warmer than in the previous year, the emergence of adult D. suzukii in the latter year occurred earlier than 2017.…”
Section: Resultssupporting
confidence: 81%
“…After the fly was first found in Spain and Italy in 2008 (Walsh et al, 2011), D. suzukii has increasingly spread into many other countries of Europe, such as Croatia, France, Portugal and Slovenia (Milek et al, 2011;Withers & Allemand, 2012). In Turkey, it was first recorded in Erzurum in 2014 (Orhan et al, 2016;Tozlu et al, 2016), and further found Ankara in 2015 (Önder et al, 2016), Bolu and Düzce in 2016 (Kaçar & Koca, 2017), Karaman in 2017 (Ögür et al, 2018) and Çanakkale in 2018 (Efil, 2018;Kasap & Özdamar, 2019). Drosophila suzukii appears to be spreading rapidly in Turkey.…”
Section: Introductionmentioning
confidence: 98%
“…It has recently been reported in many agricultural areas of Türkiye. After the D. suzukii first appeared in Türkiye, numerous investigations were conducted on its pest status (Tozlu et al, 2018;Efil, 2018;Kasap & Özdamar, 2019;Zengin & Karaca, 2019;Agbaba et al, 2020;Kaçar, 2020;Özbek-Çatal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%